2023
DOI: 10.1002/ece3.10009
|View full text |Cite
|
Sign up to set email alerts
|

Genome size variation withinCrithmum maritimum: Clues on the colonization of insular environments

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 108 publications
(141 reference statements)
0
1
0
Order By: Relevance
“…Therefore, as inferred in Cheirolophus ( Hidalgo et al . 2017 ) or in Crithmum maritimum L. ( Roxo et al 2023 ), the observed differences in genome size values among the continental A. arborescens and the Macaronesian Artemisia species could be better related to selection linked to insular condition (e.g. smaller genomes use fewer resources and show reduced genetic instability) than to the lineage divergence patterns of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as inferred in Cheirolophus ( Hidalgo et al . 2017 ) or in Crithmum maritimum L. ( Roxo et al 2023 ), the observed differences in genome size values among the continental A. arborescens and the Macaronesian Artemisia species could be better related to selection linked to insular condition (e.g. smaller genomes use fewer resources and show reduced genetic instability) than to the lineage divergence patterns of the group.…”
Section: Discussionmentioning
confidence: 99%